Promotion Strategy Or Building Brand Image On Digital/Online Media At Rizh’s Café & Resto - Stefanie Stefanie; Golan Hasan (Universitas Internasional Batam, 2023)
The purpose of implementing this project is to help build social media for the business so that it can be used and maximized as a promotional media that can help build brand awareness and brand image at the restaurant, with social media it can make it easier for these businesses to reach more people to find out about their whereabouts. the restaurant as well as implementation like this will be able to help increase sales at the restaurant in the future. In this project, the authors aim to use social media as a marketing platform for Rizh's café and restaurant. Marketing on social media can make it easier to increase brand awareness for Rizh's café and restaurant. The technique used by the author in collecting data on the practical work of this project is to visit the location and make observations.